PrEP Demographics and Disparity: The Race, Ethnicity, Gender Identity, Sex Assigned at Birth, Sexual Orientation and Age of Current PrEP Use. Issue 4 (2nd October 2022) - Hamilton, Kate; Hasney, Lara; Cohn, Tanya; Posnak, JP
ABSTRACT: Purpose: Identification of disparity in preexposure prophylaxis (PrEP) prescription by demographic group. Design: Exploratory descriptive study. Methods: Secondary data analysis of 1114 patients who received PrEP from Planned Parenthood League of Massachusetts (PPLM) between 2017 and 2020. Findings: Persons of Asian racial-identity had a higher mean PrEP prescription than the other racial groups. Persons over 30 had a higher mean PrEP prescription than those 18–29. Conclusions: Discrepancy of PrEP prescription reveals opportunities to improve PrEP delivery. Clinical Evidence: Providers of PrEP delivery and community health nurses can enhance delivery by better electronic medical charting regarding PrEP discussion and nonadherence.